A zeolite 13X/magnesium sulfate–water sorption thermal energy storage device for domestic heating - Xu, S.Z.; Lemington, q; Wang, R.Z.; Zhu, Jie (Elsevier, 2018)
A sorption thermal energy storage (TES) device for domestic heating is presented in this article. The TES device adopts the new design scenario with valve-less adsorber and separate reservoir to eliminate the large-diameter vacuum valve for vapor flow, which decreases the cost, reduces the vapor flow resistance, and improves the system reliability. The device is charged by the electric heater, which can add much flexibility to the building energy system as well as contribute to the valley filling and peak shaving from demand side management. The newly developed composite sorbent of zeolite 13X/MgSO4/ENG-TSA (expanded natural graphite treated with sulfuric acid) with the salt mass fraction of 15% in the zeolite 13X/MgSO4 mixture is tested and used in the TES device (denoted as XM15/ENG-TSA). Experimental results show that the TES device with XM15/ENG-TSA has the energy storage density of 120.3kWh∙m−3 at 250°C charging temperature and 25–90°C discharging temperature. The temperature lift is as high as 65–69°C with the adsorption and evaporating temperatures of 25°C. The impregnation of MgSO4 dramatically improves the temperature rising rate during the adsorption heat recovery process, but the specific energy storage capacity of XM15/ENG-TSA is similar to that of zeolite 13X/ENG-TSA. The effect of the impregnated MgSO4 suggests that MgSO4 can be used for low-temperature TES to relieve the self-hindrance of the hydration reaction.